A Comparative Analysis of Speech Errors in U.S. 2024 Presidential Debate - Kaonedy, Jesselyn; Nasution, Diantry Binarwaty Habibie; Sastia, May; Rangkuti, Rahmadsyah; Istiqomah, Istiqomah (Universitas Pahlawan Tuanku Tambusai, 2024)
This study focused on reviewing and analyzing the types of speech errors, comparing the frequency of such errors, and examining the reasons behind speech errors, as made by former President of the United States Donald Trump (DT) and Vice President Kamala Harris (KH) in the 2024 presidential election debate. Theory of speech error by Clark and Clark (1977) is used as the main guidance in the analysis. The debate, entitled